The Oxford textbook of clinical research ethics - Emanuel, Ezekiel J., 1957- (Oxford University Press, 2008)
The first systematic and comprehensive reference on clinical research ethics. Under the editorship of experts from the National Institute of Health of the United States, the book's 73 chapters offer a wide-ranging and systematic examination of all aspects of research with human beings. Considering historical triumphs of research as well as tragedies, the textbook provides a framework for analyzing the ethical aspects of research studies with human beings. Through both conceptual analysis and systematic reviews of empirical data, the textbook examines issues ranging from scientific validity, fair subject selection, risk benefit ration, independent review, and informed consent as well as focused consideration of international research ethics, conflicts of interests and other aspects of responsible conduct of research.